Self-care and Self-Compassion in University Student Athletes (Baltic Journal of Sport and Health Sciences, 2025)
Background: Student athletes (SA) face unique challenges in balancing academic and athletic demands, frequently impacting well-being. This study aimed to measure levels of self-care and self-compassion in SA in one university in Munster, Ireland and also aimed to investigate the relationship between these and identify some ways that universities could support SA in strengthening self-care and self-compassion behaviours.  Methods: A cross-sectional survey was used, employing shortened forms of the Mindful Self-Care Scale and the Self-Compassion Scale, as well as demographic questions. One multiple-option question asked participants to identify potential supports. Data were analysed using descriptive and inferential statistics.Results: Fifty-six responses were received. Most participants had below mean self-care and moderate self-compassion. Self-care and self-compassion were moderately positively correlated. SA who trained most frequently had lowest self-compassion. SA want tailored support with self-care and self-compassion. Support and education are needed to enable SA to develop positive self-caring and self-compassionate behaviours.Conclusion: Although it is not to possible draw causal relationships, results suggest that more self-compassionate SA are more self-caring. Support, advocacy and education is needed to enable SA to maintain and develop positive self-caring and self-compassionate behaviours.Keywords: mental health, well-being, quantitative, occupational therapy, support